Toward an Understanding of the Psychology of Stewardship - Hernandez, Morela (Academy of Management Review, 2012)
In this article I pursue two objectives. First, I refine the definition of stewardship by exploring the underlying assumptions of stewardship theory and examining the conceptual distinctiveness of the stewardship construct. Second, I propose a model of stewardship antecedents. In so doing, I discuss the structural and psychological factors that influence stewardship behaviors through psychological ownership and the ways in which stewardship behaviors can collectively create feedback loop processes to systematically shift organizational governance from agency toward stewardship.